(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Background: Obesity is a common health problem in urban population nowadays. Objective: The present study was carried out to asses the relationship of age with obesity in adult males. Methods: This cross sectional study was done in department of Physiology, Dhaka Medical College, Dhaka. For this purpose, 60 male subjects within the age range of 25 to 50 years were included in the study. Among them 30 non-obese, apparently healthy subjects were selected as control (Group A) and 30 obese subjects as case (Group B). Case and control subjects were selected from the Urban Primary Health Care Project (UPHCP), PA-2, Dhaka City Corporation, Dhaka and by personal contact during the period from January 2010 to December 2010. All the subjects were apparently healthy. Result: In this study, obese males showed significant negative correlation (p=0.032, r= -392) but non obese male showed non-significant (p=0.719, r= +0.069) positive correlation with age. Conclusion: This study concludes that, Serum iPTH level decreases with age in obese males. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16019 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 27-29